Managerial Economics - Geetika, Piyali Ghosh & Purba Roy Choudhury (New Delhi. McGraw Hill, 2022)
Managerial Economics, 3e, provides a detailed introduction of economic concepts to management students. It illustrates the technique of systematic problem solving and taking effective decisions by applying concepts of economics in different situations. With its unique integrative approach, this revised edition covers the recent developments in the interdisciplinary fields related to economics and business such as Demonetization, Jio case study, Patanjali, restriction on H1B visa, GST,Highlights of Budget 2017 and many more. Besides being a comprehensive textbook for management students, it will prove to be of great utility for the practising managers.
Keywords: MBA; Managerial Economics